2022
DOI: 10.12688/f1000research.76178.1
|View full text |Cite
|
Sign up to set email alerts
|

Temporomandibular joints disorders (TMDs) prevalence and their relation to anxiety in dental students

Abstract: Background: Temporomandibular joint disorders (TMDs) are very common disorders affecting the population and causing pain. Researchers have reported a high prevalence of TMDs among university students due to increased distress. The aims of this study were to determine the frequency of TMDs in Umm al-Qura University (UQU) dental students using the Diagnostic Criteria for Temporomandibular Disorders (DC/TMD), and to examine the relationship between anxiety, bruxism, and TMDs among those students. Methods: The DC/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…In the current study, 65.2% of the study participants were females and a majority of the respondents had stress which lead to the development of parafunctional habits progressing to temporomandibular disorders. [11][12][13][14][16][17] The most widespread parafunctional habit seen in the present study was lip biting in 30% of the students which was in agreement with the results of Malik et al whereas other studies observed chewing gums as the most common one. 16,[18][19] Thumb sucking was found to be least prevalent which was in agreement with Malik et al findings although the least prevailing parafunctional habit narrated by Butt et al was chewing gums.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, 65.2% of the study participants were females and a majority of the respondents had stress which lead to the development of parafunctional habits progressing to temporomandibular disorders. [11][12][13][14][16][17] The most widespread parafunctional habit seen in the present study was lip biting in 30% of the students which was in agreement with the results of Malik et al whereas other studies observed chewing gums as the most common one. 16,[18][19] Thumb sucking was found to be least prevalent which was in agreement with Malik et al findings although the least prevailing parafunctional habit narrated by Butt et al was chewing gums.…”
Section: Discussionsupporting
confidence: 93%
“…8,16 Prevalence of temporomandibular disorders as a consequence of oral parafunctional habits was found to be higher in dental students as reported by different studies. [13][14][15] The stress experienced by students had a significant association with clenching and grinding of teeth and a close relationship between bruxism and anxiety was also reported by Homeida et al 14 Bruxism is described as the clenching or grinding of teeth whether awake or sleeping. It's generally done unconsciously, and most individuals aren't aware of it.…”
Section: Discussionmentioning
confidence: 66%